2015
DOI: 10.1007/s40005-015-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation and application of a simple reverse phase HPLC method for in vitro dissolution studies of memantine hydrochloride tablet

Abstract: A simple, accurate and cost-effective ultraviolethigh performance liquid chromatography (UV-HPLC) assay method was developed and validated for the determination of derivatized memantine, a representative oral noncompetitive N-methyl-D-aspartate receptor antagonist to treat Alzheimer's disease, in dissolution medium. Optimized derivatization process of memantine was performed with 9-fluorenylmethylchloroformate (FMOC), and injected with the UV-HPLC system for quantitation. Derivatized memantine were separated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Speed of the paddle was adjusted to 50 rpm. CSDs or cefdinir powder filled in a gelatin capsule shell (#0), equivalent to cefdinir amount of 100 mg, was prepared and placed into a dissolution tester (Varian VK7000, Varian Inc., Santa Clara, CA, USA) [ 24 , 25 ]. At pre-determined intervals, aliquot (5 mL) of the media was collected and filtered through a membrane filter (0.45 μm pore size).…”
Section: Methodsmentioning
confidence: 99%
“…Speed of the paddle was adjusted to 50 rpm. CSDs or cefdinir powder filled in a gelatin capsule shell (#0), equivalent to cefdinir amount of 100 mg, was prepared and placed into a dissolution tester (Varian VK7000, Varian Inc., Santa Clara, CA, USA) [ 24 , 25 ]. At pre-determined intervals, aliquot (5 mL) of the media was collected and filtered through a membrane filter (0.45 μm pore size).…”
Section: Methodsmentioning
confidence: 99%
“…To apply UV/VIS or fluorescence HPLC detection of memantine, the derivatization step is required. Fluorescence detection has been used after precolumn derivatization using o‐phthaldialdehyde (OPA) , 4‐fluoro‐7‐nitro‐2,1,3‐benzoxadiazole , (2‐naphthoxy)acetyl chloride , dansyl chloride , fluorescamine , 4‐(4,5‐diphenyl‐1H‐imidazol‐2‐yl)benzoyl chloride , and 9‐fluorenylmethyl chloroformate . The RP‐HPLC using UV detection was applied for ME derivative with anthraquinone‐2‐sulfonyl chloride , 1‐fluoro‐2,4‐dinitrobenzene , 9‐fluorenylmethyl chloroformate , phenoxy acetyl chloride , and (2‐napthoxy)acetyl chloride .…”
Section: Introductionmentioning
confidence: 99%
“…From the category of non-derivative HPLC techniques, most frequently used detectors are: RID suggested by Chen et al [9], Reddy and Rao [10], Sawant and Mane [11], Sawant et al [12], and Beccera et al [13], ELSD suggested by Zhou et al [14], and Rao et al [15], MS suggested by Reddy and Rao [10] and Chavali et al [16], while CAD was used by Rystov et al [17] and Brondi et al [18]. The most utilized analytical technique was HPLC with some derivatization technique for modification of the memantine chemical structure for enabling its UV or fluorescent response, for example, using previous treatment with FMOC (9-fluorenylmethyl chloroformate): Narola et al [19] and Mokkale et al [20], or with 1-Fluoro-2,4-dinitrobenzene: Jalalizadeh et al [21] and Maeng et al [22], 4-(N-Chloroformylmethyl-N-methyl)amino-7-N,N-dimethylaminosulphonyl 2,1,3benzoxadiazole (DBD-COCL): Prapatong et al [23] and with o-phthaldialdehyde (OPA): Zarghi et al [24]. There are also HPLC methods with direct UV detection, without prior derivatization: Sujana et al [25], Rambabu et al [26], Thangabalan et al [27], Sivangaraju and Jayarao [28], Amena and Rizvan [29], Jeevitha and Pandey [30], Ravikumar et al [31], Phanshiri et al [32], Ganta and Viduadhara [33], Kumar et al [34], and Anees et al [35].…”
mentioning
confidence: 99%